Development of a single‐shot CCD‐based data acquisition system for time‐resolved X‐ray photoelectron spectroscopy at an X‐ray free‐electron laser facility. (1st January 2014) - Oura, Masaki; Wagai, Tatsuya; Chainani, Ashish; Miyawaki, Jun; Sato, Hiromi; Matsunami, Masaharu; Eguchi, Ritsuko; Kiss, Takayuki; Yamaguchi, Takashi; Nakatani, Yasuhiro; Togashi, Tadashi; Katayama, Tetsuo; et al.
<x xml:space="preserve">Abstract</x> In order to utilize high‐brilliance photon sources, such as X‐ray free‐electron lasers (XFELs), for advanced time‐resolved photoelectron spectroscopy (TR‐PES), a single‐shot CCD‐based data acquisition system combined with a high‐resolution hemispherical electron energy analyzer has been developed. The system's design enables it to be controlled by an external trigger signal for single‐shot pump–probe‐type TR‐PES. The basic performance of the system is demonstrated with an offline test, followed by online core‐level photoelectron and Auger electron spectroscopy in `single‐shot image', `shot‐to‐shot image (image‐to‐image storage or block storage)' and `shot‐to‐shot sweep' modes at soft X‐ray undulator beamline BL17SU of SPring‐8. In the offline test the typical repetition rate for image‐to‐image storage mode has been confirmed to be about 15 Hz using a conventional pulse‐generator. The function for correcting the shot‐to‐shot intensity fluctuations of the exciting photon beam, an important requirement for the TR‐PES experiments at FEL sources, has been successfully tested at BL17SU by measuring Au 4f photoelectrons with intentionally controlled photon flux. The system has also been applied to hard X‐ray PES (HAXPES) in `ordinary sweep' mode as well as shot‐to‐shot image mode at the 27 m‐long undulator beamline BL19LXU of SPring‐8 and also at the SACLA XFEL facility. The XFEL‐induced Ti 1s core‐level spectrum of La‐doped SrTiO3 is reported as a function of incident power density. The Ti 1s core‐level spectrum obtained at low power density is consistent with the spectrum obtained using the synchrotron source. At high power densities the Ti 1s core‐level spectra show space‐charge effects which are analysed using a known mean‐field model for ultrafast electron packet propagation. The results successfully confirm the capability of the present data acquisition system for carrying out the core‐level HAXPES studies of condensed matter induced by the XFEL.